Забезпечення екологічної безпеки водних об’єктів електронною підготовкою води в системах оборотного тепловодопостачання - Кюрчев, Володимир Миколайович; Кюрчев, Владимир Николаевич; Kiurchev, Volodymyr; Мовчан, Сергій Іванович; Мовчан, Сергей Иванович; Movchan, Serhii; Бережецький, О. В.; Андріанов, О. А. (ТДАТУ, 2020)
UK: В промислових умовах апробовано прилад «Hydroflow Industrial (test)» на пластинчастому теплообміннику паросилового цеху центральної компресорної станції ПрАТ «Запоріжабразив», який в широкому діапазоні температурного перепаду мастила і води довів надійність, ефективність та тривалість процесів захисту та боротьби із накипом і біообростанням на робочих поверхнях труб та обладнання. Принцип дії приладу оброблення води в теплообмінних апаратах базується на застосуванні підібраного, встановленого, контрольованого та обслуговуваного приладу імпульсної високочастотної електромагнітної обробки води, що неінтрузивно (ззовні, без порушення суцільності труби або виробу) монтується на трубу безпосередньо перед входом охолоджуючої води у випробувальний об’єкт та підключається до електричної мережі змінного струму напругою 220В. Отримані результати випробувань приладу імпульсного високочастотної електромагнітної обробки води, які проведено в широкому діапазоні температурного перепаду мастила і води, наочно довели надійність, ефективність процесів захисту та боротьби із накипом та біообростанням на робочих поверхнях труб та обладнанні і забезпечують екологічну безпеку водних об’єктів. RU: В промышленных условиях апробирован прибор «Hydroflow Industrial (test)" на пластинчатом теплообменнике паросилового цеха центральной компрессорной станции АО «Запорожабразив», который в широком диапазоне температурного перепада масла и воды доказал надежность, эффективность и продолжительность процессов защиты и борьбы с накипью и биообрастанием на рабочих поверхностях труб и оборудования. Принцип действия прибора обработки воды в теплообменных аппаратах базируется на применении подобранного, установленного, контролируемого и обслуживаемого прибора импульсной высокочастотной электромагнитной обработки воды, неинтрузивно (извне, без нарушения сплошности трубы или изделия) монтируется на трубу непосредственно перед входом охлаждающей воды в испытательный объект и подключается к электрической сети переменного тока напряжением 220В. Полученные результаты испытаний прибора импульсного высокочастотной электромагнитной обработки воды, проведенные в широком диапазоне температурного перепада масла и воды, наглядно доказали надежность, эффективность процессов защиты и борьбы с накипью и биообрастанием на рабочих поверхностях труб и оборудования, обеспечивающих экологическую безопасность водных объектов. EN: Thermal and energy supply systems that use water and other heat carriers play an important role in the country's water management system, especially in district heating systems. The rational use of water and water resources in energy supply systems is an important component not only from the technical side but also from the ecological and economic one. At the same time, reducing the use of water helps to increase the life of technological equipment, reduce the use of water and reduce the costs associated with the operation of circulating water systems. The most comprehensive and interrelated solution of the problems identified in the system of circulating water supply to the enterprises of the heat engineering and heat power industries determines the relevance of the chosen direction of research conducted in the industrial conditions of PJSC "Zaporizhzhia Abrasive Plant" (Zaporizhzhia). Hydroflow Industrial (test) impulse high-frequency electromagnetic water treatment device, which has high reliability, efficiency and long duration in the process of protection and control of scale and biofouling on working metal surfaces of pipelines and equipment of enterprises of the enterprises of the enterprises, has been tested on the operating technological equipment. The results obtained as a result of industrial testing of the pulse high-frequency electromagnetic water treatment device clearly demonstrate the significant advantages of using this method of preparation of water in the district heating systems using the device. Further development in the development of technology for the preparation and use of water in the thermal engineering and thermal power industries is the simplicity, reliability and efficiency of water preparation in the systems of circulating heat supply.
Обеспечение экологической безопасности водных объектов электронной подготовкой воды в системах оборотного тепловодоснабжения
Environmental security water objects electronic water preparation in reverse heat supply systems
Keywords: пластинчастий теплообмінний апарат; прилад імпульсної високочастотної електромагнітної обробки води; теплоелектростанції; атомні станції; системи оборотного водопостачання; пластинчатый теплообменный аппарат; прибор импульсной высокочастотной электромагнитной обработка воды; теплоэлектростанции; атомные станции; системы оборотного водоснабжения; plate parts; heat treatment apparatus; impulse of high-frequency highfrequency electromagnet water treatment; heat and power plants; atomic stations; systems of reverse water treatment; carbonate and biological processes; biological systems